PENGEMBANGAN E-BOOKLET KEANEKARAGAMAN GASTROPODA DI PANTAI NGUYAHAN UNTUK MENINGKATKAN SCIENTIFIC EXPLANATION SKILL PADA MATERI KLASIFIKASI MAKHLUK HIDUP KELAS X SMA - Mafaza, Rifda; Kurniawati, Atik (Universitas Negeri Yogyakarta, 2025)
This study aims to: (1) Determine the gastropod diversity index at Nguyahan Beach; (2) Determine the results of the booklet's feasibility test as a learning resource in improving students' Scientific Skill Explanation; (3) Determine students' responses to the use of the Nguyahan Beach gastropod e-booklet. This study is an exploratory research and development (RD) project using the 4D model (define, design, develop, disseminate). The resulting product is the Nguyahan Beach gastropod e-booklet. A feasibility collection was carried out by having material expert validators and media expert validators complete a validation questionnaire. Data collection on increasing learning interest and mastery was observed from both test and non-test results. The test results were derived from the pre-test and post-test scores, while the non-test results were obtained by having students and teachers complete a response questionnaire, serving as supporting variables. Data analysis for both tests and non-tests used standard gain. The results of this study indicate that: (1) Gastropods found at Nguyahan Beach, Gunungkidul have a high diversity index of 3.046. Consisting of 2 orders of gastropods with 10 families, 15 genera and 29 species; (2) The results of the N-Gain test in the development research were 63.67, which is classified as moderate. (3) Student responses through the readability test obtained an average percentage of 95.5% which means the product is very suitable for use in learning. Teachers can use the results of this study as an alternative teaching material in the classroom that is contextual.